2007
DOI: 10.1111/j.1744-7909.2007.00464.x
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and Growth Responses of Tomato Progenies Harboring the Betaine Alhyde Dehydrogenase Gene to Salt Stress

Abstract: The responses of five transgenic tomato (Lycopersicon esculentum Mill) lines containing the betaine aldehyde dehydrogenase (BADH) gene to salt stress were evaluated. Proline, betaine (N, N, N-trimethylglycine, hereafter betaine), chlorophyll and ion contents, BADH activity, electrolyte leakage (EL), and some growth parameters of the plants under 1.0% and 1.5% NaCl treatments were examined. The transgenic tomatoes had enhanced BADH activity and betaine content, compared to the wild type under stress conditions.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 73 publications
1
10
0
1
Order By: Relevance
“…Zhou et al (2007) found that cell membrane damage was lower in BADH expressed tomato than in wild-type under salt stress and this is in agreement with the higher relative membrane permeability and MDA (Fig. 6) of the non-transgenic plants in salinized conditions.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Zhou et al (2007) found that cell membrane damage was lower in BADH expressed tomato than in wild-type under salt stress and this is in agreement with the higher relative membrane permeability and MDA (Fig. 6) of the non-transgenic plants in salinized conditions.…”
Section: Discussionsupporting
confidence: 88%
“…Betaine accumulation plays an important role in transgenic plants. By transforming tomato with the gene responsible for betaine synthesis, Kumar et al (2004) and Zhou et al (2007) found that a higher betaine accumulation in the transgenic plants corresponded to their enhanced salt tolerance.…”
Section: Discussionmentioning
confidence: 95%
“…Several adaptations may increase the seedling's ability to cope with the consequences of drought: the ability to maintain viability at water potentials below the turgor loss point (Richards and Lamont, 1996), Rapid root growth to exploit the temporally-and spatially-restricted soil water resources (Schutz, 1999), and a high root: shoot ratio (Osunkoya et al, 1994). The reduction of productivity in many plants subjected to excessive salinity or drought is often associated with reduced photosynthetic capacity as determined by lower chlorophyll contents (Netondo et al, 2004, Zhou et al 2007. Under drought stress, the reduction of chlorophyll contents in our treatments was more obvious than that control plants, showing a more sever drought damages evidenced more pale green leaves and visible loss of turger.…”
Section: Discussionmentioning
confidence: 99%
“…• Pine resin collecting • Rattan (Daemonorops margaritae and Calamus tetradactylus) (LI et al, 2007) • Alpina katsumadai as a medicinal plant, but also as ornamental plant usable…”
Section: Findings and Inventory Databasesmentioning
confidence: 99%
See 1 more Smart Citation